PENERAPAN BUKU AL-FATIH DALAM MENINGKATKAN KEMAHIRAN MEMBACA KITAB KUNING DI PONDOK PESANTREN MADINATUL ILMI DDI SIAPO TOLI-TOLI - Titin Fatimah; Mahfudoh (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2021)
This study aims to find out how the application of the Al-Fatih Book in improving reading skills of the yellow book; and to know the steps of its application in the learning process. The research approach used is descriptive qualitative. techniques in data collection through interviews, observation, and documentation. The results of the study show that the application of the Al-Fatih Book is almost the same as other fast methods of reading the yellow book, only in its application, the Al-Fatih book uses three volumes of books, namely: the Nahwu Al-Fatih book, the Taṣrif book and the Al-Fatih practice book. munīr. while in increasing the reading skills of the students, it can be seen from the value of the practice and practice of the students in the ability or proficiency in reading the yellow book.